Fiscal decentralization and poverty alleviation: A case study of Pakistan. Issue 2 (1st July 2021) - Hussain, Sadia; Hali, Shafei Moiz; Ahmad, Riaz; Iqbal, Sumera; Iftikhar, Hamza
Abstract: According to the World Bank, the COVID‐19 pandemic is going to exacerbate the situation of poverty. It predicts that the poverty rate could rise by 0.3 to 0.7 percentage points, to around 9% in 2020. This study aims at providing insights into poverty in Pakistan and analyzes the impact of fiscal decentralization on poverty alleviation. According to the Asian Development Bank, Pakistan houses roughly 210 million poor people. This study follows the data between 1975 and 2018, applying a unit root test to station this data. The statistical models are developed with a view to the autoregressive distributed lag co‐integration technique for estimation. The findings of the study conclude that fiscal decentralization has a direct and indirect impact in eradicating poverty. We thus conclude that the government should provide autonomy to the provinces in Pakistan, as the central government alone cannot tackle and understand the local problems. Therefore, the government must adopt a fiscal decentralization policy. This study further suggests that the government should effectively utilize the progressive taxation strategy to maximize revenues and cater to poverty alleviation. 摘要: 世界银行数据表明，新冠肺炎（COVID‐19）大流行将加剧贫困。数据预测，2020年贫困率可能增加0.3‐0.7个百分点，上升至9%左右。本研究旨在研究巴基斯坦贫困，并分析财政分权对减贫造成的影响。亚洲开发银行数据显示，巴基斯坦有将近2.1亿贫困人口。本研究选取1975‐2018年的数据，并用单位根检验来平稳数据。以自回归分布滞后模型（ARDL）协整为目的，提出用于预测的统计模型。研究发现表明，财政分权对消除贫困具有直接和间接的影响。因此，我们的结论认为，巴基斯坦政府应为各省提供自治权，因为中央政府无法独自应对和理解地方问题。因此，政府需采纳财政分权政策。本研究进一步暗示，政府应有效使用累进税策略，以期将税收最大化并应对减贫。 Resumen: Según el Banco Mundial, la pandemia de COVID‐19 va a agravar la situación de pobreza. Predice que la tasa de pobreza podría aumentar de 0, 3 a 0, 7 puntos porcentuales, a alrededor del 9 por ciento en 2020. Este estudio tiene como objetivo proporcionar información sobre la pobreza en Pakistán y analiza el impacto de la descentralización fiscal en el alivio de la pobreza. Según el Banco Asiático de Desarrollo, Pakistán alberga aproximadamente a 210 millones de personas pobres. Este estudio sigue los datos entre 1975 y 2018, aplicando una prueba de raíz unitaria para estacionar estos datos. Los modelos estadísticos se desarrollan con miras a la técnica de cointegración Autoregressive Distributed Lag (ARDL) para la estimación. Los hallazgos del estudio concluyen que la descentralización fiscal tiene un impacto directo e indirecto en la erradicación de la pobreza. Por tanto, llegamos a la conclusión de que el gobierno debería otorgar autonomía a las provincias de Pakistán, ya que el gobierno central por sí solo no puede abordar y comprender los problemas locales. Por lo tanto, el gobierno debe adoptar una política de descentralización fiscal. Este estudio sugiere además que el gobierno debería utilizar eficazmente la estrategia de tributación progresiva para maximizar los ingresos y atender la mitigación de la pobreza.